(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2013)
We present a short proof of the Turán inequality for the ultraspherical polynomials. The proof makes use of the Hermite interpolation formula. A recent refinement of Turán’s inequality for ultraspherical polynomials [8] is discussed and compared with the known results.